2015
DOI: 10.1007/s40626-015-0035-5
|View full text |Cite
|
Sign up to set email alerts
|

Light-emitting diodes (LED) increase the stomata formation and chlorophyll content in Musa acuminata (AAA) ‘Nanicão Corupá’ in vitro plantlets

Abstract: Micropropagation of banana by means of different morphogenetic routes is an important source of genetically uniform, pest-and disease-free planting materials of Musa spp. Morphogenesis of in vitro grown plants are affected by light quality, light quantity and photoperiod. Light-emitting diode (LED) lighting systems have several unique advantages, including their peak spectral output, which closely coincides with the red absorption peak of chlorophyll and the reported wavelengths for maximum photosynthetic effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 40 publications
(45 reference statements)
1
19
0
Order By: Relevance
“…The stomatal size and density are indicators of plant adaptation and acclimation to environments [ 48 ]. The development of stomatal properties in tender leaves are largely affected by the light spectrum [ 11 , 49 ]. We found that the stomatal density, aperture, and conductance were highly enhanced in leaves developed in LED-mix, followed by those in LED-w, and were largely decreased for leaves in FR.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The stomatal size and density are indicators of plant adaptation and acclimation to environments [ 48 ]. The development of stomatal properties in tender leaves are largely affected by the light spectrum [ 11 , 49 ]. We found that the stomatal density, aperture, and conductance were highly enhanced in leaves developed in LED-mix, followed by those in LED-w, and were largely decreased for leaves in FR.…”
Section: Discussionmentioning
confidence: 99%
“…The changes of the stomatal density were related to the proportion of red light, and the changes in the stomatal aperture were highly related to the proportion of blue light, as well as the summed proportion of blue and red lights. The stomatal density was affected by the light quality, but the roles of monochromatic lights remained controversial since different studies reported different results [ 10 , 11 , 49 , 50 ]. On the other hand, the effect of monochromatic lights on the stomatal aperture is relatively clear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations